The Relevance of Islamic Law in the Formation of Public Policy in the Era of Globalization - Fadilla, Derri Fadilla; Arya, Muhammad Arya (Cattleya Darmaya Fortuna, 2024)
This study examines the role of Islamic law in the formationof public policy in the era of globalization. By focusing on thebasic principles of Islamic law such as social justice, economicsustainability, and protection of individual rights, this studyaims to identify the relevance and contribution of Islamic lawin formulating more just and sustainable policies. The resultsof the study indicate that the application of the principles ofsocial justice in Islamic law, such as fair distribution of wealthand attention to the weak, can enrich public policies aimed atreducing social inequality. In addition, the principle ofeconomic sustainability in Islamic law, which prioritizes wisemanagement of natural resources, has also been shown to berelevant to policies that support sustainable development.This study concludes that the integration of Islamic law inpublic policy is not only relevant, but also makes a positivecontribution in creating policies that are more inclusive, just,and in favor of the welfare of the people.